2004
DOI: 10.1002/neu.10327
|View full text |Cite
|
Sign up to set email alerts
|

Beak gape dynamics during song in the zebra finch

Abstract: Bird song is a complex communication behavior that requires the coordination of several motor systems. Sound is produced in the syrinx and then modified by the upper vocal tract, but the specific nature and dynamics of this modification are not well understood. To determine the contribution of beak movements to sound modification, we studied the beak gape patterns in zebra finches (Taeniopygia guttata). Subsyringeal air sac pressure and song were recorded together with changes in beak gape, which were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 25 publications
4
42
0
Order By: Relevance
“…For example, spectral changes in the songs of several species that were reported by Nowicki (1987) and Hoese et al (2000) appear to occur primarily above ~3.5·kHz. Similarly, spectral changes reported by Goller et al (2004) in zebra finches, Taeniopygia guttata, occur primarily over relatively high sound frequencies. Suthers and Goller (1997) also demonstrated that harmonics of fundamentals below ~3.5·kHz tend to be suppressed when northern cardinals, Cardinalis cardinalis, sing songs with relatively small beak gapes.…”
Section: Tract Filtering and Sound Radiation In A Songbirdmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, spectral changes in the songs of several species that were reported by Nowicki (1987) and Hoese et al (2000) appear to occur primarily above ~3.5·kHz. Similarly, spectral changes reported by Goller et al (2004) in zebra finches, Taeniopygia guttata, occur primarily over relatively high sound frequencies. Suthers and Goller (1997) also demonstrated that harmonics of fundamentals below ~3.5·kHz tend to be suppressed when northern cardinals, Cardinalis cardinalis, sing songs with relatively small beak gapes.…”
Section: Tract Filtering and Sound Radiation In A Songbirdmentioning
confidence: 74%
“…1B; e.g. Goller et al, 2004;Nowicki, 1987;Podos et al, 2004;Suthers and Goller, 1997;Westneat et al, 1993).…”
mentioning
confidence: 99%
“…However, most of the different call types are structurally rather similar to those we recorded and only differ in duration and repetition rate (Martella and Bucher, 1990), which makes it unlikely that the calls are produced by different articulatory patterns. Beak gape has been found to correlate with frequency changes in many bird species (Hausberger, 1991;Westneat et al, 1993;Hoese et al, 2000;Podos et al, 2004;Goller et al, 2004). In the current study we detected beak displacement in vocalizing monk parakeets of up to 6.7mm although we could not establish a quantitative relationship with frequency patterns for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigators (e.g., refs. [3][4][5][6] have shown that birdsong is often accompanied by frequency-dependent beak movements in which high fundamental frequencies are associated with a wide beak opening, or gape, compared to that at low fundamentals. The fact that experimentally fixing the gape of a singing bird at a large value increases the relative level of the second harmonic when f 0 is low (refs.…”
mentioning
confidence: 99%